Self-combustion synthesis of Na3V2(PO4)3 nanoparticles coated with carbon shell as cathode materials for sodium-ion batteries. (10th February 2015) - Wang, Hui; Jiang, Danlu; Zhang, Yan; Li, Guopeng; Lan, Xinzheng; Zhong, Honghai; Zhang, Zhongping; Jiang, Yang
Abstract: The real applications of Na3 V2 (PO4 )3 cathode material for sodium batteries have been hindered by low-cost and facile synthesis method. Herein, we report a facile self-combustion method to synthesize Na3 V2 (PO4 )3 nanoparticles coated with carbon shell (NVP/C). Using as the cathode, the NVP/C is capable of delivering the initial discharge and charge capacities of 100.72 and 111.3 mAh g −1 at the current of 0.1 C in a voltage of 2.5–3.8 V, and the capacity retention of the sample is approximately 95% of its initial specific capacity after 50th cycles. The first-principles simulation results show that the Na ions migration route prefers between two adjacent tetrahedral sites with the vacancy-hopping mechanism in a curved way, with the lowest activation energy of 0.292 eV. The diffusion coefficients DNa + at room temperature was also calculated as higher as 2.38 × 10 −9 cm 2 s −1 . The results suggest great potential of self-combustion synthesized NVP/C as cathode materials for Na-ion batteries.